Exploring the effects of interaction with a robot cat for dementia sufferers and their carers - Picking, Richard; Pike, Joanne (2017 Internet Technologies and Applications (ITA), 2017)
Research has previously demonstrated the positive effects of robotic companion pets, but while this is important from a research perspective, their cost renders their widespread use currently unfeasible. This research seeks to explore the potential of an affordable robot, with a view to making a realistic difference in quality of life for people with dementia and their carers. Early research results involving participants in the community have proved very positive.